McGraw-Hill handbook of English - Shaw, Harry, 1905- (New York : McGraw-Hill Book, 1978)
A comprehensive handbook of English grammar, usage, diction, and composition with general review exercises.
Includes index.
Keywords: English language -- Grammar -- 1950-; English language -- Composition and exercises